The determinants of efficient behavior in coordination games - Dal Bó, Pedro; Fréchette, Guillaume R.; Kim, Jeongbin (Games and economic behavior, 2021)
We study the determinants of efficient behavior in stag hunt games (2×2 symmetric coordination games with Pareto ranked equilibria) using data from eight previous experiments on stag hunt games and a new experiment that allows for a more systematic variation of parameters. We find that subjects do not necessarily play the efficient action (stag), stressing the importance of strategic uncertainty in coordination games. While the frequency of playing stag is greater when stag is risk dominant, there is still large variation in behavior that cannot be explained by risk dominance. Part of this variation is explained by the risk arising from strategic uncertainty that we measure with the size of the basin of attraction of stag. We also explore the importance of other determinants of efficient behavior and we show that the results are robust to paying subjects using the lottery method in an attempt to induce risk neutral preferences.